Diversity, Distribution, and Ecological Significance of Fishes and Macrofauna in the Koshi River Near Madhepura - Yadav, Bhagwat (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
In this research paper, the diversity, distribution, and ecological significance of fishes and macrofauna in the Koshi River near Madhepura, Bihar, were systematically investigated to assess the ecological health of this dynamic riverine ecosystem. The experiment was done at various sampling sites that represented various types of habitats in the pre-monsoon, the monsoon and the post-monsoon seasons. Fish and macrofaunal assemblages were recorded using standardized techniques of sampling, and on-site measurements of critical physico-chemical conditions including temperature, pH, dissolved oxygen, turbidity, and the velocity of flow. There were 48 macrofaunal taxa, 21 families and 9 orders showed in 48 species of fish, and the biodiversity was medium. Cypriniformes was the most common fish community and insect larvae was the densest macrofauna. The index of diversity showed that the level of species richness was higher in the habitats characterized by the high level of substrate heterogeneity and floodplain connectivity. Seasonal analysis revealed that there was a decrease in macrofaunal density in monsoon as a result of high flow disturbances and a considerable amount of recovery after the monsoon. The hypothesis test served to establish the fact that heterogeneity of habitats, seasonal flow variation and water quality had great effects on species distribution and abundance. The results point to the potential of fishes and macrofauna as useful bioindicators and demonstrate the necessity of preserving natural hydrological processes and complexity of habitats as the necessary condition to manage the Koshi River ecosystem in a sustainable manner.